Analyzing international environmental regimes : from case study to database - Breitmeier, Helmut (Global environmental accords., 2006)
Regime theory has become an increasingly influential approach to the analysis of international relations, particularly in the areas of international political economy and international environmental politics. The conceptual appeal of the idea of "governance without government"--in which a combination of different organizations and institutions supply governance to address specific problems--reflects a world in which the demand for governance is great but the familiar mechanisms for supplying it are weak. Most research on international regimes employs qualitative methods, often using case studies to develop larger theoretical arguments; but a lack of standardization makes comparative analysis difficult. Analyzing International Environmental Regimes introduces the International Regimes Database (IRD), an important methodological innovation that allows scholars to adopt a quantitative approach to the study of international regimes.The IRD is a relational database that makes it possible to compare records on specific aspects of a number of international environmental regimes that are coded using a single, well-defined set of concepts, definitions, and scales. The book first describes the database and discusses a number of methodological, technical, and architectural issues. It then illustrates the use of the IRD as an analytic tool, drawing on the database for descriptive statistics to evaluate theoretical ideas about compliance, decision rules, and the role of knowledge. A CD containing the full IRD data protocol and all the data currently in the database accompanies the book.